Strategi Pemasaran UMKM The Bake House dalam Persaingan Premium Bakery - Santi Rimadias; Alvini Ariani; Syifa Amelia; Retno Tiara Wulandari (Indonesia Economic Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy, contributing significantly to employment and national economic growth. However, increasing business competition requires MSMEs to implement effective marketing strategies to maintain their businesses and improve sales performance. This study aims to analyze the marketing strategies implemented by The Bake House, a premium bakery MSME that has evolved from a home-based business to a delivery service store. This study uses a descriptive qualitative approach through direct observation, interviews with the business owner, and interviews with five customers to understand their perceptions of product and service quality. SWOT analysis, STP (Segmentation, Targeting, Positioning), and Marketing Mix (7P) were used as analytical tools. The results show that The Bake House's main strengths lie in its premium product quality, aesthetic product presentation, and friendly customer service. However, the business still faces several challenges, including limited production capacity and inconsistent digital marketing activities. Meanwhile, the increasing demand for specialty cakes and bakery products for family events and seasonal celebrations presents significant opportunities for business expansion. Overall, the research findings indicate that a well-planned and consistent marketing strategy, particularly through digital promotions and product innovation, can help The Bake House increase its competitiveness, expand its market reach, and strengthen customer loyalty in the increasingly competitive premium bakery industry.